Red light women of the Rocky Mountains - MacKell, Jan (University of New Mexico Press, 2009)
Amazons of Arizona -- Courtesans of Colorado -- Illicit ladies of Idaho -- Madams and other women of Montana -- Nubians of New Mexico -- The undoing of Utah's soiled doves -- Wicked women of Wyoming -- Where did they all go?